Bimodal distribution of azole susceptibility in Sporothrix brasiliensis isolates in Brazil - Dos Santos, Amanda Ribeiro; Gade, Lalitha; Misas, Elizabeth; Litvintseva, Anastasia P.; Nunnally, Natalie S.; Parnell, Lindsay A.; Rajeev, Malavika; De Souza Carvalho Melhem, Marcia [UNESP]; Takahashi, Juliana Possato Fernandes; Oliboni, Gabriel Manzi; Bonfieti, Lucas Xavier; Araujo, Lisandra Siufi; et al. (American Society for Microbiology, 2024)
Sporothrix brasiliensis is an emerging zoonotic fungal pathogen that can be difficult to treat. Antifungal susceptibility testing was performed on the mold phase of a convenience sample of 61 Sporothrix spp. isolates from human and cat sporotrichosis cases in Brazil using the Clinical and Laboratory Standards Institute standard M38. A bimodal distribution of azole susceptibility was observed with 50% (28/56) of S. brasiliensis isolates showing elevated itraconazole minimum inhibitory concentrations ≥16 μg/mL. Phylogenetic analysis found the in vitro resistant isolates were not clonal and were distributed across three different S. brasiliensis clades. Single nucleotide polymorphism (SNP) analysis was performed to identify potential mechanisms of in vitro resistance. Two of the 28 resistant isolates (MIC ≥16 mg/L) had a polymorphism in the cytochrome P450 gene, cyp51, corresponding to the well-known G448S substitution inducing azole resistance in Aspergillus fumigatus. SNPs corresponding to other known mechanisms of azole resistance were not identified in the remaining 26 in vitro resistant isolates.
Keywords: antifungal agents; antifungal resistance; sporotrichosis